2022
DOI: 10.7717/peerj.12745
|View full text |Cite
|
Sign up to set email alerts
|

The performance of body mass component indices in detecting risk of musculoskeletal injuries in physically active young men and women

Abstract: Background Body composition indices can be related to musculoskeletal injuries (MI), particularly in physically active groups. However, little is known about the accuracy of these diagnoses as potential predictors of musculoskeletal injuries. Therefore, this study aims to indicate the cut-off points of relative body mass (BMI), fat mass index (FMI), skeletal muscle mass (SMI), and muscle to fat ratio (MFR) and establish its reliability in injury prediction for physically active men and women. Methods The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Similarly, a study by O’Leary et al 58 noted that in military, personal females were at higher risk for musculoskeletal injury compared with males, particularly related to the lower limbs. A recent study noted that reduced lean body mass predisposed males to injury, whereas a higher fat mass predisposed females to injury 50 . The current results indicated that a significant difference existed between male and female BF%, which could, possibly, explain the association between sex and injuries seen in the current study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, a study by O’Leary et al 58 noted that in military, personal females were at higher risk for musculoskeletal injury compared with males, particularly related to the lower limbs. A recent study noted that reduced lean body mass predisposed males to injury, whereas a higher fat mass predisposed females to injury 50 . The current results indicated that a significant difference existed between male and female BF%, which could, possibly, explain the association between sex and injuries seen in the current study.…”
Section: Discussionsupporting
confidence: 56%
“…The results of the present study indicated that the Framingham risk score and poor CVHI increased the odds of MSIs by 27% and 62%, respectively. As these risk scores are predictive of risk for atherosclerotic diseases, this relationship may help explain the association between these measures and MSIs 17,19,20,50 . Moreover, several factors included in the Framingham risk score and CVHI were independently associated with an increased likelihood of injury in the current results, making the cumulative CVD risk scores association with MSIs unsurprising.…”
Section: Discussionmentioning
confidence: 66%
“…Our previous study showed that body composition indices might help establish the optimal value of BMI and FMI to achieve a positive effect in physical fitness improvement after HIIT. Generally, using a ROC curve method effectively describes the cut-off point indicating the phenomenon’s occurrence, e.g., injury risk or failure in a training program based on chosen factors such as physical fitness [ 28 , 29 ] and body composition indices [ 25 , 26 ]. However, there is a lack of observation considering body composition indices concerning blood pressure parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The Youden index allows, based on the ROC curve sensitivity and specificity values, the optimal cut-off point to be determined [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation